SELECTION OF COVARIATES IN A LOGISTIC REGRESSION MODEL FOR THE PREDICTION OF RESISTANCE TO RICE BLAST - OSSIFO, Momate Emate; Lelis Duarte, Marciel; CARNEIRO, Antônio Policarpo Souza; Santos, Vinicios Silva dos; Martins Filho, Sebastião (Brazilian Journal of Biometrics, 2022)
Rice (Oryza sativa L.) has been one of the most consumed foods on the planet, with economic and social importance. Diseases, mainly blast, caused by the fungus Pyricularia oryzae, are limiting factors for the production of rice. The present work aimed to select covariables that can influence resistance to rice blast, using the selection strategy proposed by Collett. Logistic regression models were adjusted to predict disease resistance, using the ROC curve to assess the predictive capacity. The data used were obtained from a population of 413 plants, with phenotypic information collected in 82 countries and classified into five subpopulations. The research found that, out of over fifteen variables embedded to assess the disease, only three revealed to be relevant for the final adjusted model, namely: width of flag leaf (V4), the mean number of primary panicle branches (V8) and the amount of amylose from ground grains (V15). The variable V4 presented the most significant influence on disease resistance. Additionally, for each unit increase in V4, V8 and V15, it is expected to obtain 279.3, 31.9 and 9.4% increases, respectively, in the probability of resistance to rice blast.